2019
DOI: 10.1088/1741-2552/ab08c8
|View full text |Cite
|
Sign up to set email alerts
|

System based on subject-specific bands to recognize pedaling motor imagery: towards a BCI for lower-limb rehabilitation

Abstract: Objective. The aim of this study is to propose a recognition system of pedaling motor imagery for lower-limb rehabilitation, which uses unsupervised methods to improve the feature extraction, and consequently the class discrimination of EEG patterns. Approach. After applying a spectrogram based on short-time Fourier transform (SSTFT), both sparseness constraints and total power are used on the time-frequency representation to automatically locate the subject-specific bands that pack the highest power during pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 86 publications
3
32
0
Order By: Relevance
“…The experimental protocol from the present study will be suitable for BCI-based exoskeleton systems for rehabilitating patients with motor disorders of the lower limbs in future studies. This has been supported by the previous studies as the signals during MI have been found to facilitate the operation of lower limb exoskeleton when the classification accuracy of MI patterns, and even the motor intention, was high [54], [55].…”
Section: Feasibility Study and Applicationssupporting
confidence: 76%
“…The experimental protocol from the present study will be suitable for BCI-based exoskeleton systems for rehabilitating patients with motor disorders of the lower limbs in future studies. This has been supported by the previous studies as the signals during MI have been found to facilitate the operation of lower limb exoskeleton when the classification accuracy of MI patterns, and even the motor intention, was high [54], [55].…”
Section: Feasibility Study and Applicationssupporting
confidence: 76%
“…The feasibility of inducing neurological recovery in paraplegic patients by long term training with a BCI-based gait protocol was shown in [5]. In addition, BCI-based control of virtual object [6], robotic arm [7][8][9], robotic prosthetic [10,11], wheelchair [12], and various rehabilitation devices [13][14][15][16] were also reported in previous research.…”
Section: Introductionmentioning
confidence: 81%
“…The analysis of single events in the EEG, in turn, is relatively rarely used, especially at short time intervals [25,51]. Comparative analysis has shown [52][53][54] that by single implementations of short (up to 500 ms) EEG segments, it is possible to identify the type of visual stimulus that indicates, for example, the direction of movement and the areas of the brain involved in its processing. In addition, even shorter EEG epochs (up to 200 ms) may be sufficient in identifying the readiness potential, indicating the lateralization of the upcoming motor act.…”
Section: Discussionmentioning
confidence: 99%